Constitutional literacy in times of crisis - DE VISSER, Maartje (Institutional Knowledge at Singapore Management University, 2020)
At the same time she announced her withdrawal from public life in 2018, former US Supreme Court Justice Sandra Day O’Connor made a passionate plea for “all citizens to understand our Constitution and unique system of government, and participate actively in their communities.”441 The timing coincided with the halfway mark of Donald Trump’s term in presidency, a president who has very publicly declared his knowledge of the US Constitution, but whose understanding of it has regularly been called into question.442 At its foundation, the democratic legitimacy of a government arguably presupposes a working familiarity with the constitution qua social contract. How can a constitutional system claim to be based on popular sovereignty if its populace is ignorant of the source and scope of its government’s powers and responsibilities? Only when citizens are aware of the rights they have can they vindicate perceived violations thereof. Familiarity with the scope of State powers and inter-institutional balance allows us individuals to perform our collective role as constitutional guardians and to do so responsibly, be it at the ballot box, by challenging unlawful State actions or by effectively using freedom of information laws.